2018
DOI: 10.1002/pds.4580
|View full text |Cite
|
Sign up to set email alerts
|

Ascertainment and validation of major bleeding events in a primary care database

Abstract: Major GI and UG bleeding events ascertained from THIN using read codes require validation using additional information to prevent outcome misclassification. The absence of validation may lead to overestimated incidence rates of major bleeding for GI and UG bleeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Lastly, Delate et al recommended a manual chart review to validate warfarin-related bleeding events from administrative data [13]. Ruigomez et al also advocated additional information to prevent misclassification as regards major GI or urogenital bleeding events [14]. Our findings are in line with these previous results and have highlighted differential measures of accuracy between ICH and GI.…”
Section: Discussionsupporting
confidence: 87%
“…Lastly, Delate et al recommended a manual chart review to validate warfarin-related bleeding events from administrative data [13]. Ruigomez et al also advocated additional information to prevent misclassification as regards major GI or urogenital bleeding events [14]. Our findings are in line with these previous results and have highlighted differential measures of accuracy between ICH and GI.…”
Section: Discussionsupporting
confidence: 87%
“…Such an approach authorizes a more accurate estimate of haemorrhagic risk. A recent study showed that the manual medical record review was a necessary step especially for gastrointestinal and urogenital bleeds, improving the true estimated incidence rates; in comparison, the codes used alone in database overestimated the incidence rates. Furthermore, such a medical review overcomes the classification bias related to retrospective analysis of data based on hospital discharge diagnosis (ICD‐10 codes) without medical validation .…”
Section: Discussionmentioning
confidence: 99%
“…To validate outcomes in THIN, anonymized patient profiles, including any free-text comments related to the event, are manually reviewed. The necessity and added value of this approach have been demonstrated in a previous validation study, which identified that major gastrointestinal and urogenital bleeding rates are overestimated in the absence of manual review [24]. For the Swedish nationwide health registries, a prior validation study has demonstrated high sensitivity (85.5%) and specificity (95.9%) for the detection of major bleeding events associated with hospitalization [25].…”
Section: Safety and Effectiveness Outcomesmentioning
confidence: 99%